A new genus and a new Costa Rican species of Endocephalites (Chrysomelidae: Eumolpinae: Eumolpini) - Flowers, R. Wills (Zootaxa, 2003)
Thysanomeros new genus is described from Costa Rica. The new species Thysanomeros ulateae Flowers is described, and Prionodera jacobyi Lefèvre is transfered to Thysanomeros NEW COMBINATION and designated as the type species. The new genus belongs in the informal group Endocephalites of the eumolpine tribe Eumolpini.